Chaperonin GroEL–GroES Functions as both Alternating and Non-Alternating Engines. Issue 15 (31st July 2016) - Yamamoto, Daisuke; Ando, Toshio
Abstract: A double ring-shaped GroEL consisting of 14 ATPase subunits assists protein folding, together with co-chaperonin GroES. The dynamic GroEL–GroES interaction is actively involved in the chaperonin reaction. Therefore, revealing this dynamic interaction is a key to understanding the operation principle of GroEL. Nevertheless, how this interaction proceeds in the reaction cycle has long been controversial. Here, we directly imaged GroEL–GroES interaction in the presence of disulfide-reduced α-lactalbumin as a substrate protein using high-speed atomic force microscopy. This real-time imaging revealed the occurrence of primary, symmetric GroEL:GroES2 and secondary, asymmetric GroEL:GroES1 complexes. Remarkably, the reaction was observed to often branch into main and side pathways. In the main pathway, alternate binding and release of GroES occurs at the two rings, indicating tight cooperation between the two rings. In the side pathway, however, this cooperation is disrupted, resulting in the interruption of alternating rhythm. From various properties observed for both pathways, we provide mechanistic insight into the alternate and non-alternate operations of the two-engine system. Graphical Abstract: Highlights: The dynamic interaction of GroES with the two rings of chaperonin GroEL in the presence of disulfide-reduced α-lactalbumin is visualized by high-speed atomic force microscopy. The chaperonin cycle proceeds through the formation of symmetric GroEL:GroES2 complex and its decomposition to the asymmetric GroEL:GroES1 complex. Both positive cooperativity of GroES dissociation and negative cooperativity of ADP release engender between the two rings of GroEL, so that the two rings operate alternately. Nevertheless, these cooperative effects often vanish likely due to incomplete nucleotide exchange at GroES-free ring, resulting in non-alternate operation of the two rings.